The Education of Inuit Youth in Nunavik: Teachers’ and Students’ Perspectives - Garakani, Tatiana (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2016)
This article draws on data collected in Nunavik between 2011 and 2014 to describe the perceptions of Inuit students and their teachers (Inuit and non-Inuit) about their motivation, the purpose of schooling, the quality of their relationships, and the pedagogical choices and approaches that influence their perseverance. Informed by critical Indigenous methodologies, the research was conducted with the approval of Kativik Ilisarniliriniq, the School Board of Nunavik. A wide range of research tools was used to facilitate participation by teachers from the French, English, and Inuit sectors, in elementary (Kindergarten to Grade 6) and high school (Grades 7 to 11), and participation by students from the French and English sectors (Grades 8 to 11).